Phytochemistry, Pharmacology and Botanical Aspects of Hortia Species in the Search for Molecules with Bioactive Potential – A Review - Portela, Roberto Campos; Fiuza, Tatiana de Sousa; Paula, José Realino de; Borges, Leonardo Luiz (Pharmacognosy Reviews)
Hortia Vand. is a Neotropical genus of Rutaceae. Ten species occurs in South America in Atlantic forests, in Brazilian Savannah (Cerrado) and especially in the Amazon. Among these species, H. brasiliana is used to treat fevers, malaria, diarrhea, vomiting and liver diseases. H. oreadica is popularly use as antipyretic, substitute for quina, as tonic and stomach. This paper aims to give an overview of the Hortia genus, focusing on morphological, phytochemical and biological activities to stimulate new studies about these species. The main substances and derivatives isolated from Hortia species include dictamnine, γ-fagarine, skimmianine, robustine, flindersine, N-methyl-flindersine, rutaecarpine, hortiamine, hortiacine, seselin, 5-methoxyseselin, scoparon, guianin, limonin and nerolidol. These substances present properties such as antimicrobial, antifungal, anti-inflammatory, spasmolytic, anti-diabetic, anti-atherosclerotic, antiulcerogenic, anticancer, hepatoprotective, neuroprotective, immunosuppressive, antimalarial, acaricidal, larvicidal and antifeed. Several of these activities could justify the popular uses of the Hortia species.
Keywords: Active compounds; Biological activity; Brazilian Cerrado; Medicinal plants; Rutaceae; Taxonomy